Avifaunal Diversity on the Kasetsart University Campus, Chalermphrakiat Sakon Nakhon Province - Prateep Duengkae (Agriculture and Natural Resources, 2010)
A study of the diversity of bird species was conducted from July 2006 until the end of June 2007 on the campus of Kasetsart University in Chalermphrakiat Sakon Nakhon province. The study involved a survey of the bird species and the production of a checklist, with conservation status and abundance. The results indicated that 79 species were present, belonging to 10 orders and 23 families, of which 53 were resident, 26 were migrant and 3 were passage migrant species. According to the Wildlife Preservation and Protection Act 2003, 76 of these species are protected. Based on the status of species listed in the Wildlife Thai Red List (2007), this area had only one threatened species. This study is the first report on bird diversity in the area. Recommendations are given for monitoring diversity and for limiting human disturbance in order to maintain biodiversity.